Characterizing the Dependence on Non-timber Forest Products Among Communities Living Around Forest Conservation Areas in Marrupa-Mecula Corridor, Niassa Special Reserve, Niassa Province of Mozambique - Lubega, Gerald; Falcão, Mário Paulo; Ssekandi, Joseph; Ribeiro, Natasha Sofia (Frontiers in Forests and Global Change, 2022)
The role of forests across the world has been recognized as key natural assets which offer a number of goods and services, especially to communities adjacent to them. Given this role, there have been limited efforts to determine the factors characterizing this dependence of communities on non-timber forest resources. This study surveyed and assess different factors influencing household dependence on NTFPs in Mecula Niassa Province of Mozambique. 377 household members from 5 villages attended the interview while employing proportional random sampling. Data analysis was done using descriptive statistics and binary logistic regression. The study revealed that 90.9% of the households participate in collecting, producing, and selling non-timber forest products. Twenty factors or characteristics were found to have a significant association with dependence on forest resources. These include; the availability of Non-timber forest products, taking a collection of non-timber forest products as a family job, strong cultural attachment to forests, seasonal engagement in collection, nearby forests being home for community leaders, distance to a nearby forest, the housing needs of forests, forests being a major source of medicine and forests being a resource for education institutions. Other factors are; forests being a major source of household food security, ready income for households, a tourist attraction in the area, and affordability of distance to markets. The binary logistic regression revealed sex, age, education, family size, and time spent in the area as significantly associated with dependence on non-timber forest resources. Additionally, forest fires, strong cultural attachment to forests; seasonal engagement in collection, nearby forests being homes for community leaders; distance to a nearby forest, housing needs, a major source of medicine; education, household food security; ready income, tourist attraction and affordability of a distance to markets were found to have a significant influence. On the other hand, scary dangerous wild animals; restriction of cultivation in non-gazetted forests, restriction of hunting in non-gazetted forests, and forest fires negatively affected the dependence on NTFPs/resources. As a way of achieving sustainable utilization of NTFPs, management plans and strategies need to incorporate these factors characterizing dependence on NTFPs.